PENGARUH SIKAP SISWA TERHADAP KEPEDULIAN PADA LINGKUNGAN DI MADRASAH ALIYAH MUHAMMADIYAH LIMBUNG KABUPATEN GOWA - Aminah Aminah; Yermi Yermi (Pascasarjana Universitas Negeri Makassar, 2022)
Aminah. The Effect of Students' Attitudes on Concern for the Environment at Madrasah Aliyah Muhammadiyah Limbung, Gowa Regency. This study aims to determine the effect of students' attitudes on concern for the environment at Madrasah Aliyah Muhammadiyah, Gowa Regency. This type of research is a survey. Data was collected using a questionnaire. The sample in the study was 67 people. The data were analyzed using descriptive and inferential analysis. The results of the analysis show that: (1) the attitude and concern of students towards the environment at Madrasah Aliyah Muhammadiyah Limbung Gowa Regency is in the high category. (2) there is a positive influence on students' attitudes towards students' environmental concerns at Madrasah Aliyah Muhammadiyah Limbung Gowa Regency, with a regression coefficient of 0.408 meaning that if students' attitudes are improved it will have a positive effect on environmental awareness of 0.408 from the magnitude of the increase in student.